Transformasi Interaksi Metabolisme Manusia-Alam: Resiliensi Masyarakat Lahan Rawa Gambut dalam Menghadapi Perubahan Iklim - Rahmawati; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2025)
Peatland degradation, particularly the increasing risks of fires and flooding due to climate change, necessitates transformative efforts by communities to sustain their livelihoods. This study aims to examine the social resilience of the community in Jambu Baru Village in terms of maintaining their climate-affected livelihoods. The research uses a qualitative method with a phenomenological approach. Data were collected through participant observation, in-depth interviews, and documentation. The findings show that climate change significantly affects the livelihoods of the Jambu Baru Village community, which relies heavily on peatland resources. Resilience is demonstrated through adaptation based on local knowledge. The community's resilience is reflected in diversifying livelihood sources, where households are not dependent on a single income source. Each family typically engages in multiple livelihood activities, such as maiwak, manggau kayu galam, manetes uwey, mamuai banyir, beje management, and others. Furthermore, community resilience is supported by strengthened social solidarity. Resilience emerges from the integration of enhanced economic adaptation, utilization of social capital, and environmental conservation, which are key to sustainable livelihoods. The community also develops local wisdom to reduce the risks of fire and flood disasters. Academically, it is recommended to conduct comparative research on community resilience across different peatland communities to further explore the forms of resilience in the face of increasingly complex climate change impacts. Practically, it is advised that communities develop innovations to produce products with higher economic value.